Erratum (Annals of Medical Research, 2026)
In the article by Keser S, et al., entitled “An examination of the ocular surface parameters of patients with non-exophthalmic Graves disease” published in Ann Med Res. 2023;30(5):607–610, the authors informed us that the year “2022” had been inadvertently included in the description of the study period in the Abstract and Materials and Methods sections.Following editorial evaluation, it was deemed necessary to amend the study period to 2023 to ensure clarity and consistency throughout the manuscript.This correction does not affect the results, statistical analyses, or conclusions of the study. However, we believe that this minor revision improves the overall clarity and consistency of the manuscript.The relevant sections have been corrected accordingly. You can access the updated article PDF via the following link: https://annalsmedres.org/index.php/aomr/article/view/4438